Disparities in Opioid Use Disorder Treatment Admissions in the United States - Peter J. Mallow; Michael Mercado; Michael Topmiller (Journal of Health Economics and Outcomes Research)
**Objectives:** The Cincinnati region has been at the epicenter of the nation’s unfolding opioid epidemic. The objectives of this study were twofold: (1) to compare the Cincinnati region to the United States in length of time to obtain treatment and planned medication-assisted therapy for the treatment for opioid use disorder (OUD); and (2) to assess racial disparities within the Cincinnati region in wait time and type of treatment.